Chromosome-level assembly of the horseshoe crab genome provides insights into its genome evolution - Prashant Shingate (Nature Portfolio, 2020)
Horseshoe crabs have been morphologically stable across evolutionary time. Here, the authors generate a chromosome-level assembly for the mangrove horseshoe crab, with implications for innate immunity, and challenging assumptions about the role of genome duplication in adaptive radiation.